IMPLIKASI PENINGKATAN ANGGARAN MILITER INDONESIA TERHADAP FENOMENA SECURITY DILEMMA DI ASSOCIATION OF SOUTHEAST ASIAN NATIONS (ASEAN): MALAYSIA DAN SINGAPURA TAHUN 2014-2016 - Hardiansyah "; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Changes and an increase in military spending ASEAN countries is the fact dynamics armament southeast asia today. nevertheless, on the other hand countries in southeast asia seek to "create" peace through regional collaborations to always maintain regional peace. the article is meant to know further indoneisa’s background in increasing its military expenditure through describing its armed forces’ defense policy especially in its military expenditure and by seeing how far the impact of indonesia’s military expenditure increase for phenomenon of security dilemma in ASEAN especially in two countries, malaysia and singapore This research is using realism perspective, in this perspective of realism emphasizes the existence of structures in viewing the phenomenon of international relations. For structural realism (offensive and defensive) each country is seen to have the same behavior, policies and interests. Backed by the Nation State level analysis and Theory of Regional Security Complex, The concept leads to qualitative methods and library research for references. Indonesia's military expenditure increasing effect in the Security Dilemma in the ASEAN which caused a balance of power between three countries: Indonesia, Malaysia and Singapore, as one point said by Hass the balance meaning Equilibrium means what it seems to imply to the uninitiated layman: an exact equilibrium of power between two or more contending parties.Keyword: Security Dilemma, Military Expenditure, ASEAN, Balance Of Power